Quinary mab phase solid solution material, method of making, and lithium-ion anode electrode sheet

CN123017961APending Publication Date: 2026-10-30NORTHWESTERN POLYTECHNICAL UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611212912.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其中,三元单M位MAB相是选取Cr、Mo等单一过渡金属作为M位组分,但该体系根源在于M位仅存在单一金属原子,材料电子结构、层间距、锂吸附界面能可调控范围极小,不存在多金属协同作用来丰富储锂活性位点、降低锂离子扩散能垒,最终表现为可逆容量偏低、大电流倍率性能较差;同时单一金属构成的M-B层缺少晶格畸变带来的形变缓冲能力,锂反复嵌脱时层状结构极易发生不可逆膨胀、滑移甚至粉化,长循环过程容量衰减速度快,无法适配长寿命储能场景

Benefits of technology

本发明提供的六方晶系型五元MAB相固溶体材料,以M位过渡金属近等摩尔原子级均匀固溶带来1.1R高构型熵,粉体维持完整层状微观形貌,通过三种原子尺寸差异显著,充分激活晶格畸变、迟滞扩散与多元素“鸡尾酒”协同效应,从晶体结构层面拓宽锂离子嵌脱活性位点、扩大层间扩散通道、缓冲充放电过程晶格体积形变,多元素“鸡尾酒”效应同步调节费米能级附近的电子态密度,依靠高熵设计理念带来的高混合熵、晶格畸变、迟滞扩散与多元素协同效应,拓宽锂离子嵌脱活性位点、缓冲充放电体积形变,A位元素既作为A层原子与M-B层交替堆叠形成层状结构,又作为可刻蚀组分保留后续衍生MBene的可能性,同时承担层间电荷传输通道功能,其金属性导电为电极倍率性能提供保障。B位元素B与M位金属形成M-B共价键骨架,构建刚性M-B层,硼的轻量化特性有助于提升材料的质量比容量,B原子的多原子键合特征可与锂离子产生高反应活性,从材料本征结构层面提升储锂容量、倍率性能与长循环稳定性,拓宽储锂活性位点并降低锂离子扩散能垒。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017961A_ABST
    Figure CN123017961A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of MAB phase solid solution, and particularly relates to a quinary MAB phase solid solution material, a preparation method and a lithium ion negative electrode sheet. The chemical formula of the quinary MAB phase solid solution material is M2AB2, M is a transition metal selected from three of chromium, molybdenum, yttrium, iron and manganese, the atomic radius ratio of the three transition metals is 0.9-0.95:1:1.2-1.3, the molar ratio of each transition metal is 0.9-1.2:0.9-1.2:1, and A is aluminum, gallium or indium. By means of near-equal-molar random occupation of the three transition metals at the M position, the three atomic size differences are utilized, the configuration entropy ΔS=R·ln3≈1.1R is constructed, the crystal lattice distortion, the lag diffusion and the multi-element 'cocktail' synergistic effect are fully activated, the lithium ion intercalation and deintercalation active sites are widened from the crystal structure level, the interlayer diffusion channel is expanded, the lattice volume change in the charging and discharging process is buffered, and the lithium storage capacity, the rate performance and the long cycle stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of MAB phase solid solution technology, specifically relating to a pentagonal MAB phase solid solution material and its preparation method, and a lithium-ion negative electrode sheet. Background Technology

[0002] Layered transition metal borides (MAB phases), with their unique layered crystal structure, excellent intrinsic electronic conductivity, and the ability to selectively etch two-dimensional MBene, are considered highly promising novel functional materials and precursors for energy storage electrodes, showing broad application prospects in high-performance lithium-ion batteries, electrocatalytic hydrogen evolution, and high-temperature structural materials. Their typical alternating stacked MB and A layers provide abundant insertion / extraction sites and smooth two-dimensional diffusion channels for lithium ions, while their good metallic conductivity ensures rapid charge transport capabilities of the electrode. However, traditional low-element MAB phase materials face multiple limitations in lithium-ion storage applications: On the one hand, the M site is usually composed of only one or two transition metal elements, resulting in a narrow composition design space and relatively limited means of controlling the number of lithium storage active sites and electronic structure, making it difficult to further improve the reversible capacity and reaction kinetics of the material; on the other hand, the structure of a single-component MAB phase is not stable enough, and the layered structure is prone to volume expansion and structural pulverization during long-term lithium insertion and extraction, leading to rapid capacity decay and electrode cycle life that cannot meet the application requirements of long-life energy storage devices; in addition, a single metal system cannot leverage the synergistic effect of multiple components, making it difficult to reduce the lithium storage reaction energy barrier through lattice engineering and interface control, and the high current rate performance and comprehensive energy storage characteristics of the material are difficult to improve significantly, thus limiting the performance ceiling and application scenarios of the entire system.

[0003] In recent years, to overcome the inherent performance limitations of traditional low-element MAB phases, researchers have introduced the concept of entropy material design into MAB phase systems. This involves constructing MAB phase solid solutions by introducing multiple principal transition metals at the M-site, such as the ternary single-metal MAB phase system. The ternary single-M-site MAB phase selects a single transition metal such as Cr or Mo as the M-site component. However, the root cause of this system is that only a single metal atom exists at the M-site. The electronic structure, interlayer spacing, and lithium adsorption interface energy are extremely limited in their controllability. There is no multi-metal synergy to enrich lithium storage active sites and reduce the lithium-ion diffusion barrier, ultimately resulting in low reversible capacity and poor high-current-rate performance. Furthermore, the single-metal MB layer lacks the deformation buffering capacity caused by lattice distortion. During repeated lithium insertion and extraction, the layered structure is prone to irreversible expansion, slippage, and even pulverization, leading to rapid capacity decay during long cycles and making it unsuitable for long-lifetime energy storage scenarios. Based on this, existing researchers have developed quaternary MAB phase systems, such as Mo, through M-site bimetallic solid solutions. 4 / 3 Y 2 / 3AlB2, Mo 4 / 3 Sc 2 / 3In the i-MAB phases such as AlB2, although this ordering brings structural diversity, the configurational entropy of the dual-M element system, ΔS = R·ln2 ≈ 0.69R, means that the thermodynamic high-entropy stabilization effect and hysteretic diffusion effect cannot be fully activated; this Mo 1- x M x In the AlB system, Zr and Ti are completely insoluble, while only Cr, Ta, Nb, and V can be partially dissolved at high temperatures, significantly limiting the solid solubility and disorder of the binary system. However, the d-electronic structure of the two M elements has limited dimensions of regulation, resulting in insufficient means to control lithium-ion adsorption energy and diffusion barriers, thus failing to fully leverage the material's performance advantages. Summary of the Invention

[0004] The purpose of this invention is to provide a pentagonal MAB phase solid solution material, its preparation method, and a lithium-ion anode sheet. By constructing an M2AB2 system solid solution material, the M site is occupied by three transition metals in near equimolar random positions, with a configuration entropy ΔS = R·ln3 ≈ 1.1R. The significant differences in the atomic sizes of the three metals bring about a strong lattice distortion effect, causing the M site to exhibit atomic-level disordered solid solution rather than in-plane ordered. The multi-element "cocktail" effect simultaneously regulates the electronic state density near the Fermi level, broadens the lithium storage active sites, and reduces the lithium-ion diffusion barrier, thereby breaking through the performance limitations of low-element MAB phases. Relying on the high-entropy design concept, which brings high mixing entropy, lattice distortion, hysteresis diffusion, and multi-element synergistic effect, the lithium-ion intercalation and deintercalation active sites are broadened, and the charge and discharge volume deformation is buffered. From the intrinsic structure level of the material, the lithium storage capacity, rate performance, and long-cycle stability are improved, achieving a comprehensive leap in the overall performance of lithium storage.

[0005] To achieve the above objectives, the specific technical solution provided by the present invention is as follows: The first objective of this invention is to provide a pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is M2AB2, wherein M is a transition metal selected from three of chromium, molybdenum, yttrium, iron, and manganese, the atomic radius ratio of the three transition metals is 0.9-0.95:1:1.2-1.3, the molar ratio of each transition metal is 0.9-1.2:0.9-1.2:1, A is aluminum, gallium, or indium, and the pentagonal MAB phase solid solution material is hexagonal.

[0006] Furthermore, the pentagonal MAB phase solid solution material has the space group P63 / mmc and the chemical formula Cr. 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, Fe 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 or Mn 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2.

[0007] Furthermore, when the chemical formula of the pentagonal MAB phase solid solution material is Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 has a layered crystal structure with alternating MB and Al layers along the c-axis. The unit cell parameters are: a=5.38 Å, b=5.38 Å, c=22.39 Å, α=90°, β=90°, γ=120°.

[0008] A second objective of this invention is to provide a method for preparing the above-mentioned pentagonal MAB phase solid solution material, comprising the following steps: S1. Based on the chemical formula M2AB2, weigh out transition metal powder, A powder and boron powder; mix and grind them, then perform wet ball milling, and dry to obtain mixed powder.

[0009] S2. The mixed powder is pressed to form a green body, and sintered at room temperature to 1200℃~1800℃ under a protective gas atmosphere to obtain a pentagonal MAB phase solid solution material.

[0010] Furthermore, during the sintering process, the protective gas is argon, and the temperature is increased to 700℃~900℃ at a rate of 3℃ / min~7℃ / min, and then increased to 1200℃~1800℃ at a rate of 2℃ / min~4℃ / min. The sintering holding time is 180min~220min.

[0011] Furthermore, during the pressing process, the pressure is 15MPa to 25MPa, the holding time is 2min to 5min, and the density of the green body is ≥55%.

[0012] Furthermore, the particle size of the transition metal powder, A powder, and boron powder is 200-300 mesh.

[0013] Furthermore, during the wet ball milling process, anhydrous ethanol is used as the medium, the ball-to-material ratio is 4-6:1, the rotation speed is 200-300 r / min, and the milling time is 25-35 min.

[0014] The third objective of this invention is to provide a lithium-ion negative electrode sheet, which is prepared by mixing active material, carbon black, and binder, adding solvent, grinding into a slurry, coating onto a substrate, removing the solvent, and then rolling to obtain the lithium-ion negative electrode sheet, wherein the loading of active material is 1.0 mg / cm³. 2 ~1.5mg / cm 2 The active material is the aforementioned pentagonal MAB phase solid solution material.

[0015] Furthermore, the coating thickness is 80μm to 120μm, and the mass ratio of active material, carbon black, and binder is 6 to 8: 2 to 4: 1.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: The hexagonal pentagonal MAB phase solid solution material provided by this invention achieves a high configurational entropy of 1.1R through near equimolar atomic-level uniform solid solution of transition metals at the M site. The powder maintains a complete layered microstructure. Through significant differences in the three atomic sizes, it fully activates lattice distortion, hysteresis diffusion, and the synergistic effect of the multi-element "cocktail". From the crystal structure level, it broadens the active sites for lithium-ion insertion and extraction, expands the interlayer diffusion channels, and buffers the lattice volume deformation during charge and discharge. The multi-element "cocktail" effect synchronously regulates the electronic state density near the Fermi level. Relying on the high-entropy design concept, the high mixing entropy, lattice distortion, hysteresis diffusion, and multi-element synergistic effect broaden the active sites for lithium-ion insertion and extraction and buffer the volume deformation during charge and discharge. The A-site element serves as both an A-layer atom and an MB-layer atom, alternately stacking to form a layered structure, and as an etchable component to retain the possibility of subsequent MBene derivation. It also serves as an interlayer charge transport channel, and its metallic conductivity ensures the rate performance of the electrode. The B-site element B forms a covalent bond framework with the M-site metal, constructing a rigid MB layer. The lightweight properties of boron help improve the specific capacity of the material. The multi-atom bonding characteristics of B atoms can produce high reactivity with lithium ions, thereby improving the lithium storage capacity, rate performance and long-cycle stability from the intrinsic structural level of the material, broadening the active sites for lithium storage and reducing the lithium ion diffusion barrier.

[0017] The preferred pentagonal MAB phase solid solution of this invention is Cr. 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 exhibits a layered crystal structure along the c-axis, with alternating MB and Al layers. The three elements Cr, Mo, and Y at the M-site each have a clear synergistic function. Cr exhibits a pseudogap at the Fermi level, demonstrating intrinsically high structural stability. Simultaneously, Cr's 3d electronic states dominate the density of states near the Fermi level, allowing for the tuning of the material's metallic conductivity and providing a good electron transport channel for lithium-ion storage. Mo also exhibits a local minimum at the Fermi level, demonstrating high structural stability. The introduction of Mo can adjust the MB layer bond strength, and Mo doping can reduce the band gap, shifting the Fermi level upwards into the conduction band, improving intrinsic electronic conductivity and increasing the lithium-ion diffusion channel. Y has the largest atomic radius among the three selected transition metals, creating a significant atomic size difference with Cr and Mo, introducing strong lattice distortion. Furthermore, as a rare earth element, Y's 4d / 5s electronic states participate in electronic reconstruction near the Fermi level, and the i-MAB phase formed with Mo can exist stably below 2000 K, exhibiting thermodynamic compatibility.

[0018] When the pentagonal MAB phase solid solution material is used as the negative electrode of lithium-ion battery, the reversible capacity stabilizes at 490.3 mAh / g after 600 cycles at a current density of 0.1 A / g, and the capacity retention rate reaches 80.4% after 10,000 cycles at an ultra-high current density of 5 A / g. The rate performance, reversible lithium storage capacity and ultra-long cycle stability comprehensively surpass the low-element MAB comparison system. Attached Figure Description

[0019] Figure 1 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2.

[0020] Figure 2 The pentagonal MAB phase Nb prepared for Comparative Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2.

[0021] Figure 3 The pentagonal MAB phase W prepared for Comparative Example 2 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2.

[0022] Figure 4 The pentagonal MAB phase Hf prepared for Comparative Example 3 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2.

[0023] Figure 5 The pentagonal MAB phase V prepared for Comparative Example 4 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2.

[0024] Figure 6 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 Crystal structure diagram of AlB2.

[0025] Figure 7 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 Microstructure diagram of AlB2.

[0026] Figure 8 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y2 / 3 Elemental distribution map of AlB2 Figure 8 In the image, a and b are scanning electron microscope images at different locations, c is the elemental distribution map of C, d is the elemental distribution map of Mo, e is the elemental distribution map of Y, f is the elemental distribution map of Al, g is the elemental distribution map of B, and f is the elemental distribution map of EDS.

[0027] Figure 9 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The CV curve of AlB2 as the negative electrode at a scan rate of 0.1 A / g for five cycles.

[0028] Figure 10 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The first five isothermal charge-discharge curves of AlB2 as the negative electrode at a current density of 0.1 A / g.

[0029] Figure 11 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 Rate performance diagram of AlB2 as negative electrode.

[0030] Figure 12 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The graph shows the long-cycle performance of AlB2 as the negative electrode at a current density of 0.1 A / g.

[0031] Figure 13 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The graph shows the long-cycle performance of AlB2 as the negative electrode at a current density of 1A / g.

[0032] Figure 14 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The graph shows the long-cycle performance of AlB2 as the negative electrode at a current density of 3A / g.

[0033] Figure 15 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The graph shows the long-cycle performance of AlB2 as the negative electrode at a current density of 5A / g. Detailed Implementation

[0034] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0036] In recent years, to overcome the inherent performance limitations of traditional low-level MAB phases, researchers have introduced high-entropy material design concepts into MAB phase systems. This involves constructing multi-principal MAB phase solid solutions by introducing multiple principal transition metals at the M-site. These materials typically possess superior structural stability and richer performance regulation dimensions. They can leverage the thermodynamic stabilization effect of high mixing entropy, lattice distortion effect, retarded diffusion effect, and the synergistic effect of multi-element "cocktails" to simultaneously expand lithium storage active sites, optimize ion transport kinetics, and improve cycle stability, providing a novel technical path for the performance leap of MAB phase materials. Although high-entropy MAX phase materials have been extensively reported, and some studies have initially achieved the synthesis and energy storage performance verification of quaternary MAB phases, this ordering, while bringing structural diversity, results in a configuration entropy of ΔS = R·ln2 ≈ 0.69R for the dual-M element system, meaning the thermodynamic high-entropy stabilization effect and retarded diffusion effect cannot be fully activated. 1-x M x In the AlB system, Zr and Ti are completely insoluble, while only Cr, Ta, Nb, and V can be partially dissolved at high temperatures. The solid solubility and disorder of the binary system are significantly limited. The d-electronic structure of the two M elements has limited dimensions of regulation, and there are insufficient means to regulate the lithium-ion adsorption energy and diffusion barrier, resulting in a ceiling on reversible capacity and rate performance.

[0037] The current mainstream research approach in the field of pentagonal layered borides consists of two main types: ternary monometallic MAB phase systems and M-site bimetallic solid solution quaternary MAB phase systems. However, their entropy effects cannot be fully released, leading to a limited number of lithium storage active sites, a lack of multi-element synergistic effects, and weak stability of the layered structure. This results in inherent performance limitations in reversible capacity, rate performance, and cycle life. Therefore, developing a pentagonal MAB phase solid solution with uniform composition, high phase purity, and stable structure, and establishing an efficient, controllable, and scalable preparation process, has become a key challenge in advancing MAB phase energy storage materials.

[0038] Based on this, the present invention provides a pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is M2AB2, wherein M is a transition metal selected from three of chromium, molybdenum, yttrium, iron and manganese, the atomic radius ratio of the three transition metals is 0.9-0.95:1:1.2-1.3, the molar ratio of each transition metal is 0.9-1.2:0.9-1.2:1, A is aluminum, gallium or indium, and the pentagonal MAB phase solid solution material is hexagonal.

[0039] It should be noted that the hexagonal pentagonal MAB phase solid solution constructed in this invention achieves a high configurational entropy of 1.1R through near equimolar atomic-level uniform solid solution of transition metals at the M site. The powder maintains a complete layered microstructure. Through significant differences in the three atomic sizes, the synergistic effects of lattice distortion, hysteresis diffusion, and multi-element "cocktail" are fully activated. This broadens the lithium-ion intercalation / deintercalation active sites, expands the interlayer diffusion channels, and buffers the lattice volume deformation during charge and discharge processes at the crystal structure level. The multi-element "cocktail" effect simultaneously regulates the electronic state density near the Fermi level. Relying on the high mixing entropy, lattice distortion, hysteresis diffusion, and multi-element synergistic effects brought about by the high entropy design concept, the lithium-ion intercalation / deintercalation active sites are broadened, and the charge and discharge volume deformation is buffered. This improves the lithium storage capacity, rate performance, and long-cycle stability at the intrinsic structural level of the material, broadens the lithium storage active sites, and reduces the lithium-ion diffusion barrier.

[0040] In a preferred embodiment, the pentagonal MAB phase solid solution material is space group P63 / mmc with the chemical formula Cr. 2 / 3Mo 2 / 3 Y 2 / 3 AlB2, Fe 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 or Mn 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2. The atomic radius ratios of Cr, Mo, and Y are 0.914:1:1.286, Fe, Mo, and Y are 0.9:1:1.286, and Mn, Mo, and Y are 0.907:1:1.286. When the chemical formula of the pentagonal MAB phase solid solution material is Cr... 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 has a layered crystal structure with alternating MB and Al layers along the c-axis. The unit cell parameters are: a=5.38 Å, b=5.38 Å, c=22.39 Å, α=90°, β=90°, γ=120°.

[0041] It should be noted that when M is chromium, molybdenum, or yttrium, and A is aluminum, the chemical formula of the hexagonal pentagonal MAB phase solid solution is Cr. 2 / 3 Mo 2 / 3Y 2 / 3 In AlB2, the M-site lattice sites are occupied by nearly equimolar uniform amounts of Cr, Mo, and Y transition metal atoms, forming a layered crystal structure along the c-axis with alternating MB and Al layers. Each of the three elements at the M-site has a clear cooperative function. Cr exhibits a pseudogap at the Fermi level, possessing intrinsically high structural stability. Simultaneously, the 3d electronic states of Cr dominate the density of states near the Fermi level, allowing for the tuning of the material's metallic conductivity and providing a good electron transport channel for lithium-ion storage. Mo also exhibits a local minimum at the Fermi level, demonstrating high structural stability. The introduction of Mo can adjust the MB layer bond strength. Theoretical calculations show that Mo doping can reduce the band gap, shift the Fermi level upwards into the conduction band, improve intrinsic electronic conductivity, and increase the lithium-ion diffusion channel. Among the three selected transition metals, Y has the largest atomic radius, resulting in a significant atomic size difference with Cr and Mo, introducing strong lattice distortion. Simultaneously, as a rare earth element, Y's 4d / 5s electronic states participate in electronic reconstruction near the Fermi level, and the i-MAB phase formed with Mo can exist stably below 2000 K, demonstrating the thermodynamic compatibility of the Y-Mo combination. The near equimolar ratio of the three elements results in a configuration entropy of 1.1R, entering the high-entropy stable region. Al at the A-site serves both as an alternating A-layer atom and MB layer to form a layered structure, and as an etchable component to retain the potential for subsequent MBene derivation. The Al layer also functions as an interlayer charge transport channel, and its metallic conductivity ensures the electrode's rate performance. B at the B-site forms a covalently bonded MB framework with the M-site metal, constructing a rigid MB layer. Boron's lightweight properties help improve the material's specific capacity, and the multi-atom bonding characteristics of B atoms enable high reactivity with lithium ions.

[0042] This invention is based on a synergistic design addressing the three major requirements of high capacity, high rate capability, and long cycle life of lithium-ion battery anodes, and constructs a Cr... 2 / 3 Mo 2 / 3 Y 2 / 3The AlB2 pentagonal system, through precise definition of cell parameters and element molar ratio ranges, relies on the high entropy design concept to bring high mixing entropy, lattice distortion, hysteresis diffusion, and multi-element synergistic effects. This broadens the lithium-ion intercalation / deintercalation active sites and buffers charge-discharge volume deformation, improving lithium storage capacity, rate performance, and long-cycle stability from the intrinsic structural level. In terms of high capacity, the lightweight and multi-atom bonding of boron provides a high theoretical capacity, while the d-electronic states of Cr / Mo provide abundant lithium storage active sites. The synergy of these three factors results in a reversible capacity of 490.3 mAh / g at 0.1 A / g. In terms of high rate performance, Mo improves intrinsic electronic conductivity, the Al layer provides rapid interlayer electron transport, and the lithium-ion channels broadened by lattice distortion allow the material to maintain excellent capacity even at a high current of 5 A / g. In terms of long-term cycling, the strong lattice distortion introduced by Y acts as a buffer layer for lithium insertion / extraction volume deformation, and the thermodynamic stabilization effect of high mixing entropy suppresses phase separation in long-term cycling. The two work together to achieve a capacity retention of 80.4% after 10,000 cycles at 5 A / g.

[0043] In addition, the present invention also provides a method for preparing the above-mentioned pentagonal MAB phase solid solution material, comprising the following steps: S1. Based on the chemical formula M2AB2, weigh out transition metal powder, A powder and boron powder; mix and grind them, then perform wet ball milling, and dry to obtain mixed powder.

[0044] The particle size of the transition metal powder, A powder and boron powder is 200 mesh to 300 mesh. Since A powder has high-temperature volatility, the volatile components are compensated by optimizing the raw material ratio and using excess compensation for high-temperature volatility. In a specific embodiment, 5% excess compensation for high-temperature volatility is used.

[0045] It is understood that this invention employs wet ball milling, utilizing the wetting and dispersing effects of a liquid medium to achieve uniform mixing of the raw materials and refine the particle size of the mixed powder. During the wet ball milling process, anhydrous ethanol is used as the medium, the ball-to-material ratio is 4–6:1, the rotation speed is 200–300 r / min, and the milling time is 25–35 min. In this invention, the purity of the transition metal powder, A powder, and boron powder is ≥99%. After wet ball milling, the powder needs to be dried in a vacuum oven at 60℃ for 12 h to obtain the mixed powder.

[0046] S2. The mixed powder is pressed to form a green body, and sintered at room temperature to 1200℃~1800℃ under a protective gas atmosphere to obtain a pentagonal MAB phase solid solution material.

[0047] In some embodiments, during the pressing process, the mixed powder is loaded into a mold at a pressure of 15 MPa to 25 MPa, and the holding time is 2 min to 5 min, resulting in a green body density ≥ 55%. It is understood that the green body...

[0048] In some embodiments, during the sintering process, argon is used as the protective gas, and the temperature is increased to 700℃~900℃ at a rate of 3℃ / min~7℃ / min, and then increased to 1200℃~1800℃ at a rate of 2℃ / min~4℃ / min. The sintering holding time is 180min~220min. By segmenting the temperature rise to match the diffusion kinetics of different metal atoms, high-purity, low-oxygen flowing argon gas isolates oxidation throughout the process.

[0049] It should be noted that, addressing the three major challenges of differences in diffusion rates among multiple metals, high-temperature volatilization of aluminum, and trace oxygen-induced impurity phases, this invention employs a one-step solid-state reaction preparation process. By limiting parameters across all stages, including raw material specifications, ball milling and mixing, cold pressing, sintering, and post-treatment, an efficient, controllable, and scalable preparation process is established. This results in a single-phase homogeneous layered crystal structure, achieving atomically uniform elemental distribution, excellent structural stability, and rapid lithium-ion transport kinetics. High-purity single-phase pentagonal solid solutions are synthesized, with a total impurity phase content ≤3%, high crystallinity, and no elemental segregation. The process is simple and controllable, possessing industrial-scale production potential. By segmented heating to match the diffusion kinetics of different metal atoms and using high-purity, low-oxygen flowing argon gas to isolate oxidation throughout the process, the preparation process is simplified and the production threshold is lowered while ensuring high product performance. This improves the consistency of composition and performance across different batches of products, providing reliable technical support for the large-scale preparation of pentagonal MAB phase materials and their practical application in energy storage.

[0050] This invention also provides a lithium-ion negative electrode sheet, which is prepared by mixing active material, carbon black, and binder in a mass ratio of 6-8:2-4:1, adding solvent and grinding into a slurry, coating it onto a substrate to a thickness of 80μm-120μm, removing the solvent, and then rolling to obtain the lithium-ion negative electrode sheet, wherein the loading of active material is 1.0mg / cm³. 2 ~1.5mg / cm 2 The active material is the aforementioned pentagonal MAB phase solid solution material.

[0051] It is understood that the binder, matrix, and solvent are materials conventionally used by those skilled in the art in preparing lithium-ion negative electrode sheets. In this invention, the binder is polyvinylidene fluoride, the matrix is ​​a 10μm thick copper foil, and the solvent is NMP. The solvent is removed by drying in a 60°C vacuum oven for 20 hours to completely remove the NMP solvent. Subsequently, the dried copper foil is rolled under 10MPa pressure and punched into a 12mm diameter circular electrode sheet.

[0052] This invention uses a pentagonal MAB phase solid solution material as the active material. Regarding high capacity, the lightweight nature and multi-atom bonding of boron provide a high theoretical capacity, while the d-electronic states of Cr / Mo provide abundant lithium storage active sites. Mo improves intrinsic electronic conductivity, and the Al layer provides rapid interlayer electron transport. Combined with the lithium-ion channels broadened by lattice distortion, the material maintains excellent capacity even at a high current of 5 A / g. Regarding long cycling, the strong lattice distortion introduced by yttrium acts as a buffer layer for lithium insertion / extraction volume deformation, and the high mixing entropy thermodynamic stabilizing effect suppresses phase separation during long-cycle cycling. The synergistic effect of these two factors results in a capacity retention of 80.4% after 10,000 cycles at 5 A / g.

[0053] It should be noted that the pentagonal MAB phase solid solution material provided by this invention is not limited to applications in lithium-ion anode sheets. The purpose of the lithium-ion anode sheet provided by this invention is to illustrate the performance advantages of the pentagonal MAB phase solid solution material. The pentagonal MAB phase solid solution material can also be used in other battery materials, as well as in electrocatalysts in the field of electrocatalysis, in functional ceramics to protect high-temperature wear-resistant structural ceramics, in electromagnetic wave absorbing coating materials, etc.; it can also be used in composite materials to protect metal-based and resin-based reinforced fillers, etc.

[0054] The following specific examples will provide further explanation.

[0055] Example 1 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is Cr 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0056] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, based on the chemical formula Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of each element Cr:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses chromium powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with an excess of 5% aluminum powder to compensate for sintering volatilization; weigh out 0.3413g of chromium powder, 0.6899g of molybdenum powder, 0.5003g of yttrium powder, 0.2657g of aluminum powder, and 0.2028g of boron powder.

[0057] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0058] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0059] S4. Place the billet into an alumina crucible and purge it with 99.999% high-purity argon gas for 30 minutes in a tube furnace until the oxygen content in the furnace drops to 8 ppm. The argon gas flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The billet is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black single-phase pentagonal MAB phase solid solution powder.

[0060] Example 2 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is Mn 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0061] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, based on the chemical formula Mn 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of each element Mn:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses manganese powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with 5% excess aluminum powder to compensate for sintering volatilization; weigh out 0.276g of manganese powder, 0.303g of molybdenum powder, 0.237g of yttrium powder, 0.395g of aluminum powder, and 0.789g of boron powder.

[0062] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0063] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0064] S4. Place the billet into an alumina crucible and purge it with 99.999% high-purity argon gas for 30 minutes in a tube furnace until the oxygen content in the furnace drops to 8 ppm. The argon gas flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The billet is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black single-phase pentagonal MAB phase solid solution powder.

[0065] Example 3 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is Fe. 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0066] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, based on the chemical formula Fe 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of Fe:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses iron powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with 5% excess aluminum powder to compensate for sintering volatilization. 0.364g of iron powder, 0.686g of molybdenum powder, 0.497g of yttrium powder, 0.251g of aluminum powder, and 0.202g of boron powder are weighed.

[0067] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0068] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0069] S4. Place the billet into an alumina crucible and purge it with 99.999% high-purity argon gas for 30 minutes in a tube furnace until the oxygen content in the furnace drops to 8 ppm. The argon gas flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The billet is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black single-phase pentagonal MAB phase solid solution powder.

[0070] Comparative Example 1 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is Nb 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0071] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, based on the chemical formula Nb 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of Nb:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses niobium powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh. Aluminum powder is added in excess at 5% to compensate for volatilization during sintering. 0.541g of niobium powder, 0.612g of molybdenum powder, 0.444g of yttrium powder, 0.224g of aluminum powder, and 0.180g of boron powder are weighed.

[0072] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0073] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0074] S4. Place the billet into an alumina crucible and purge the tube furnace with 99.999% high-purity argon for 30 minutes until the oxygen content in the furnace drops to 8 ppm. The argon flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The furnace is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black solid solution powder.

[0075] Comparative Example 2 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is W 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0076] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, according to the chemical formula W 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of each element W:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses chromium powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with aluminum powder in excess at 5% to compensate for sintering volatilization; and weighs 0.8461g of tungsten powder, 0.4836g of molybdenum powder, 0.3507g of yttrium powder, 0.1774g of aluminum powder, and 0.1422g of boron powder.

[0077] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0078] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0079] S4. Place the billet into an alumina crucible and purge the tube furnace with 99.999% high-purity argon for 30 minutes until the oxygen content in the furnace drops to 8 ppm. The argon flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The furnace is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black solid solution powder.

[0080] Comparative Example 3 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is Hf 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0081] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, based on the chemical formula Hf 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of each element Hf:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses hafnium powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with aluminum powder in excess at 5% to compensate for sintering volatilization; weigh out 0.8317g of hafnium powder, 0.4896g of molybdenum powder, 0.3551g of yttrium powder, 0.1796g of aluminum powder, and 0.1439g of boron powder.

[0082] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0083] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0084] S4. Place the billet into an alumina crucible and purge the tube furnace with 99.999% high-purity argon for 30 minutes until the oxygen content in the furnace drops to 8 ppm. The argon flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The furnace is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black solid solution powder.

[0085] Comparative Example 4 A pentagonal MAB phase solid solution material, wherein the chemical formula of the pentagonal MAB phase solid solution material is V 2 / 3 Mo 2 / 3 Y 2 / 3AlB2.

[0086] The preparation method of the above-mentioned pentagonal MAB phase solid solution material includes the following steps: S1, according to chemical formula V 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, with the stoichiometric molar ratio of each element V:Mo:Y:Al:B = 2.1:2.3:1.8:3:6, uses vanadium powder, molybdenum powder, yttrium powder, aluminum powder, and boron powder. All raw materials have a purity ≥99.9% and a particle size of 250 mesh, with an excess of 5% aluminum powder to compensate for sintering volatilization. 0.3377g of vanadium powder, 0.6967g of molybdenum powder, 0.5054g of yttrium powder, 0.2556g of aluminum powder, and 0.2048g of boron powder are weighed.

[0087] S2. Mix the above powders and dry grind them in an agate mortar for 8 minutes to achieve initial mixing. Then, transfer them to a planetary ball mill, use 5 mL of anhydrous ethanol as the medium, a ball-to-powder ratio of 5:1, a rotation speed of 200 r / min, and ball mill for 30 minutes. After ball milling, place the mixed powder in a vacuum oven at 60℃ and dry for 12 hours to obtain a mixed powder with no agglomeration and uniform color.

[0088] S3. The mixed powder is loaded into a steel mold with a diameter of 15mm and held under pressure of 20MPa for 3 minutes to obtain a cylindrical blank with a diameter of 15mm and a thickness of 2.5mm. The density of the blank is about 58%.

[0089] S4. Place the billet into an alumina crucible and purge the tube furnace with 99.999% high-purity argon for 30 minutes until the oxygen content in the furnace drops to 8 ppm. The argon flow rate is 80 mL / min throughout the sintering process. The heating rate is 5℃ / min from room temperature to 800℃ and 3℃ / min from 800℃ to 1500℃. The furnace is held at 1500℃ for 200 minutes. After sintering, the tube furnace is allowed to cool naturally to room temperature. The cooled billet is then removed and polished with 500-mesh SiC sandpaper to remove the surface oxide layer and impurities. After polishing, the billet is ground thoroughly to 250 mesh in an agate mortar to obtain a gray-black solid solution powder.

[0090] The structural tests were performed on the pentagonal MAB phase solid solution materials prepared in Example 1 and Comparative Examples 1 to 4, and the results are shown below.

[0091] Figure 1 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2. Figure 2 The pentagonal MAB phase Nb prepared for Comparative Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2. Figure 3 The pentagonal MAB phase W prepared for Comparative Example 2 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2. Figure 4 The pentagonal MAB phase Hf prepared for Comparative Example 3 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2. Figure 5 The pentagonal MAB phase V prepared for Comparative Example 4 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 XRD pattern of AlB2. (See image.) Figures 1 to 5 As shown, in Example 1, Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The experimental XRD values ​​in AlB2 are consistent with the calculated XRD values. However, the experimental XRD data in Comparative Examples 1 to 4 differ significantly from the calculated XRD data, demonstrating that Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 was successfully synthesized, while Nb 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, W 2 / 3Mo 2 / 3 Y 2 / 3 AlB2, Hf2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, V 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 synthesis failed. Compared to W 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, V 2 / 3 Mo 2 / 3Y 2 / 3 AlB2, Nb 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, Hf 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, Cr 2 / 3 Mo 2 / 3 Y 2 / 3 In AlB2, the atomic radius of Cr is slightly smaller than that of Mo, resulting in a small, controllable lattice compressive stress after substitution. The significantly larger radius of Y leads to moderate lattice expansion. The contraction and expansion cancel each other out the overall distortion, and the size mismatch is within the stable solid solution range. Relying on the original lattice framework of Mo, a uniform substitution solid solution can be stably formed, thus enabling the successful synthesis of a single-phase MAB phase. The radii of W and Mo are almost the same, making it impossible to construct an effective stress balance, resulting in insufficient solid solution driving force. The radius of V is too small compared to Mo, and the weak distortion makes it difficult to form an entropy stabilization effect. The radii of Nb and Hf are both larger than those of Mo. When combined with Y, they will continuously expand the lattice in one direction, resulting in excessive overall distortion stress and severe lattice framework distortion, making it impossible to maintain the original crystal structure. Therefore, it is difficult to synthesize the target single-phase solid solution MAB phase.

[0092] Figure 6 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 Crystal structure diagram of AlB2. (See diagram below.) Figure 6As shown, the stacking directions of the unit cell's a and b basal planes and the c-axis are marked. The cyan-green spheres represent Y atoms, the light purple spheres represent Mo atoms, and the dark blue spheres represent Cr atoms. These three types of metal atoms uniformly occupy the M sites in the crystal structure. The light blue spheres are Al atoms at the A sites between layers, and the green spheres form the B atoms of the rigid framework. The overall structure is periodically and alternately stacked along the c-axis. A stable two-dimensional covalent network of boron atoms serves as the rigid support framework for the entire crystal, supporting the randomly dissolved Cr, Mo, and Y metal layers. Al atoms are interspersed within the layers. A weak interlayer bonding interface is formed between two adjacent M metal layers. Relying on the different atomic radii of the three M site atoms, the smaller Cr appropriately shrinks the local lattice, the standard-sized Mo maintains the overall framework of the parent hexagonal lattice, and the large-radius Y appropriately expands the lattice and weakens the bonding between M and Al. The lattice distortions brought by different atoms can be balanced and canceled out. The configuration entropy stabilization effect ensures that the multi-principal layered crystal structure can exist stably. The weak interlayer bonding of Al atoms also provides a structural basis for the subsequent alkaline etching and exfoliation to prepare MBene two-dimensional sheet materials.

[0093] Figure 7 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 Microstructure diagram of AlB2. Figure 8 The pentagonal MAB phase Cr prepared in Example 1 of this invention 2 / 3 Mo 2 / 3 Y 2 / 3 Elemental distribution map of AlB2 Figure 8 In the image, a and b are scanning electron microscope (SEM) images at different locations, c is the elemental distribution map of carbon (C), d is the elemental distribution map of molybdenum (Mo), e is the elemental distribution map of yttrium (Y), f is the elemental distribution map of al (Al), g is the elemental distribution map of boron (B), and f is the elemental distribution map of ethylene glycol (EDS). Figure 7 and Figure 8As shown, the powder mainly consists of blocky, broken particles of varying sizes. Some particles exhibit clear layered textures on their surfaces, confirming the material's natural layered crystal structure. The overall particle morphology is dense and complete, without significant large-area pores or severe fragmentation. Following this are the EDS surface distribution maps for the five elements Cr, Mo, Y, Al, and B. The signal enrichment regions of each element highly overlap with the particle outlines within the SEM field of view. All five elements are uniformly dispersed within the particle area, without obvious local agglomeration, segregation, or exposed / missing areas. This directly demonstrates that the three M-site metal atoms of Cr, Mo, and Y have achieved uniform solid solution occupancy, and the two components, Al and B, are also uniformly embedded in the crystal structure, resulting in a homogeneous single-phase solid solution powder. The EDS energy spectrum curves and atomic percentage quantitative data in the lower right corner further corroborate the elemental composition (as shown in Table 1). The atomic percentages of Cr, Mo, and Y are close to each other, basically matching the experimentally predetermined molar ratios. Al... The proportion of elemental atoms is relatively higher. Due to its light element characteristics, the EDS detection signal of element B is weak, but the overall distribution is uniform. The combined morphology and elemental characterization results show that the MAB phase powder prepared in this study has a complete microstructure and uniform elemental composition. The three transition metals have been successfully and uniformly and disorderedly dissolved in the crystal, with no obvious impurity phase agglomeration problem. The overall composition of the material is good.

[0094] Table 1. Quantitative data on atomic percentage in EDS energy dispersive spectroscopy. Cr 23.3 Mo 18.5 Y 23.2 Al 35.1 The Cr prepared in Example 1 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 is used as an active material in lithium-ion anode plates, and then assembled to form lithium-ion batteries to counteract the effects of Cr. 2 / 3 Mo 2 / 3 Y 2 / 3 The performance evaluation of AlB2 as an active material includes the following steps: Preparation of lithium-ion negative electrode sheet: The Cr prepared in Example 1 was used... 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 powder, conductive carbon black, and PVDF binder were mixed in a mass ratio of 7:2:1, and 150 μL of NMP solvent was added. The mixture was ground for 45 min to form a uniform black slurry, which was then coated onto a 10 μm thick copper foil, resulting in a wet film thickness of 100 μm. The slurry was dried in a vacuum oven at 60℃ for 20 h to completely remove the NMP solvent. The dried copper foil was then rolled under 10 MPa pressure and punched into circular electrode sheets with a diameter of 12 mm. Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 powder loading: 1.2 mg / cm³ 2 .

[0095] Button cell assembly: CR2032 half cells were assembled in an argon glove box with water and oxygen contents of <0.1ppm; lithium metal sheets were used as counter and reference electrodes, Celgard 2400 polypropylene microporous membranes were used as separators, and 1.0mol / L LiPF6 was dissolved in EC / DEC (volume ratio 1:1) mixed solvent as electrolyte.

[0096] Figure 9 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 as the negative electrode at 0.1 mV·s -1 The CV curve for five rotations at the scan rate. (Example) Figure 9 As shown, the horizontal axis represents voltage, and the vertical axis represents response current. During the first round of the black curve at the cathode, a significant reduction peak appears in the 0.6V–0.8V range, mainly corresponding to the activation reaction of the electrolyte on the electrode surface, the formation of the solid electrolyte interphase (SEI) film, and the process of ion insertion into the layered MAB phase lattice. The oxidation current at the anode corresponds to the ion insertion / extraction behavior. From the red, blue, green, and purple curves of the second to fifth rounds, it can be seen that the CV profiles of subsequent cycles highly overlap, the difference caused by the irreversible polarization in the first round rapidly decreases, the reduction characteristic peak gradually weakens and tends to stabilize, and the magnitude and curve shape of the oxidation and reduction currents hardly shift significantly during the cycling process. This indicates that after the initial electrochemical activation, the oxidation-reduction reaction of internal ion insertion / extraction in this MAB phase material exhibits excellent reversibility. The electrode structure remains stable during repeated electrochemical cycles, with low polarization and the interface reaction gradually stabilizing, demonstrating good cycling stability and reversible electrochemical kinetics.

[0097] Figure 10 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The isothermal charge-discharge curves of AlB2 as the negative electrode for the first five cycles at a current density of 0.1 A / g. (See figure) Figure 10As shown, the horizontal axis represents specific capacity, and the vertical axis represents voltage, with a test voltage window of 0V to 3.0V. During the first discharge cycle, significant irreversible capacity loss occurs in the low-voltage range, stemming from irreversible side reactions such as the formation of the SEI passivation film on the electrode surface and electrolyte decomposition. The shape of the first charging curve differs significantly from subsequent cycles. From the second to the fifth cycle, the charge-discharge curves gradually overlap significantly, the charge-discharge voltage plateau and capacity change trend stabilize, the polarization difference narrows slightly, and the reversible specific capacity steadily increases and stabilizes during cycling. This indicates that after the initial electrochemical activation, the reversibility of the electrochemical reactions of ion insertion and extraction is continuously optimized, the layered crystal structure remains stable during charge-discharge, the electrode polarization gradually decreases, and the overall cycle stability is excellent. This verifies that the MAB phase material possesses stable electrochemical lithium storage behavior and good structural tolerance.

[0098] Figure 11 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 Rate performance diagram of AlB2 as the negative electrode. (See diagram) Figure 11 As shown, the horizontal axis represents the number of cycles, and the vertical axis represents the discharge specific capacity. The values ​​marked in the figure represent the test current density at the corresponding stage, in A·g. -1 Initially 0.1 A·g -1 The first-cycle discharge specific capacity can reach 200 mAh·g at low current density. -1 The initial slight capacity decay mainly stemmed from irreversible processes such as SEI film formation; subsequently, the current was gradually increased to 0.2 A·g. -1 0.3A·g -1 0.5A·g -1 1A·g -1 2A·g -1 As the current density increases, the polarization gradually rises, and the discharge specific capacity that the material can achieve gradually decreases, reaching a maximum of 2 A·g. -1 Under high current conditions, the capacity drops to its lowest level throughout the entire operation; when the current density returns to its initial value of 0.1 A·g... -1 At that time, the discharge specific capacity can recover rapidly and be stably maintained at close to 100 A·g. -1 The good capacity recovery indicates that the layered crystal structure of the MAB phase material did not undergo irreversible damage during high-current charging and discharging, and it has excellent structural stability and outstanding rate reversible recovery capability, with good overall electrochemical rate characteristics.

[0099] Figure 12 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The long-cycle performance of AlB2 as an anode at a current density of 0.1 A / g is shown in the figure. Figure 12As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis corresponds to the coulombic efficiency. Initially, the electrode capacity experienced a brief, slight drop, which is typical of the gradual formation of the SEI film at the electrode interface and the activation by electrolyte wetting. After this, the specific capacity entered a stage of continuous and steady increase during activation. As the cycles continued, the electrolyte fully penetrated the electrode, ion transport channels were gradually opened, and more active sites within the material were gradually activated and utilized. The capacity continued to increase and then stabilized after 500 cycles, remaining stable at approximately 500 A·g. -1 The high level of efficiency; the coulombic efficiency remained stable at close to 100% throughout the entire process, with only a very slight drop in the later stage, indicating that the redox reaction of ion insertion and extraction during charging and discharging is highly reversible and there are very few side reactions. After hundreds of long cycles, the layered crystal structure did not collapse or pulverize, and the overall structural stability is excellent. This fully demonstrates that the MAB phase electrode of this invention has excellent long-cycle service stability and excellent electrochemical reversibility.

[0100] Figure 13 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The long-cycle performance of AlB2 as an anode at a current density of 1 A / g is shown in the figure. Figure 13 As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. During the initial cycling phase, the capacity briefly drops slightly, corresponding to the initial activation stage as the SEI film at the electrode interface stabilizes. Subsequently, as the electrolyte fully wets the electrode interior with each cycle, the active sites are gradually activated, and the discharge specific capacity shows a gradual and steady upward trend. There is no sharp drop in capacity throughout the cycle, and the capacity still steadily increases to nearly 100 A·g at the end of 600 cycles. -1 The overall coulombic efficiency remained close to 100% with slight fluctuations after stabilization, and there were almost no obvious irreversible side reactions throughout the process. This indicates that even under high current and rapid charge and discharge conditions, the layered crystal structure of the MAB phase can still maintain stability, the ion insertion and extraction process has excellent reversibility, the electrode is not prone to structural pulverization and collapse, and it has excellent high current long cycle stability and electrochemical reversibility.

[0101] Figure 14 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The long-cycle performance of AlB2 as an anode at a current density of 3A / g is shown in the figure. Figure 14As shown, the horizontal axis represents the number of cycles, the left vertical axis represents the discharge specific capacity, and the right vertical axis represents the coulombic efficiency. The capacity fluctuated slightly in the initial stage of the test, which is the initial activation stage as the SEI film at the electrode interface gradually stabilizes and the electrolyte fully wets the electrode system. After a brief trough, the capacity entered a state of continuous and slow increase. As cycling progressed, more energy storage active sites within the material were gradually activated, and the ion transport channels were continuously optimized. No sudden, precipitous capacity decay occurred throughout the entire process. After 1200 cycles, the capacity remained steadily increasing and maintained at a considerable level. The corresponding coulombic efficiency remained consistently close to 100% after the initial activation, with only extremely small fluctuations. This means that under the harsh conditions of ultra-high rate rapid charge and discharge, the electrochemical reactions of ion insertion and extraction are highly reversible, with minimal electrolyte decomposition and interfacial side reactions. Relying on the lattice structure stability brought by medium-entropy solid solution, the layered crystal framework did not undergo significant structural pulverization or collapse failure during long-term high-current cycling. This fully demonstrates that the MAB phase material of this invention possesses extremely strong structural tolerance and excellent ultra-high rate and ultra-long cycle service stability.

[0102] Figure 15 For the present invention Cr 2 / 3 Mo 2 / 3 Y 2 / 3 The long-cycle performance of AlB2 as an anode at a current density of 5 A / g is shown in the figure. Figure 15 As shown, the initial capacity fluctuation is due to the construction of the SEI film and the activation of the electrode. The capacity then slowly and slightly decreases before stabilizing. It still maintains a considerable capacity after tens of thousands of cycles, and the coulombic efficiency after stabilization is always close to 100%. This proves that the MAB phase lattice structure can withstand the stress impact of tens of thousands of ion insertion and extraction at ultra-high magnification. The structure is not easy to collapse and pulverize, and it has excellent electrochemical reversibility and extremely strong stability in ultra-high magnification and ultra-long cycle service.

[0103] In summary, the Cr provided by this invention 2 / 3 Mo 2 / 3 Y 2 / 3AlB2 is a hexagonal single-phase pentagonal MAB phase solid solution with atomically uniform solid solution of Cr, Mo, and Y at the M site. The system configuration entropy reaches 1.1R, and the powder maintains a complete layered microstructure. With a one-step solid-state process featuring segmented temperature control, low-oxygen argon protection, and aluminum component excess compensation, high-purity products can be stably reproduced. Lithium-ion anodes prepared with this material can achieve a reversible capacity of 490.3 mAh / g after 600 cycles at 0.1 A / g, and a capacity retention rate of 80.4% after 10,000 cycles at a high current of 5 A / g. The rate reversibility and long-cycle stability are significantly better than traditional ternary and quaternary MAB phase materials. By employing precise raw material molar ratios (Cr:Mo:Y:Al:B = 2.1:2.3:1.8:3:6), limiting raw material particle size, and utilizing a complete set of quantitative process parameters including ball milling and sintering, along with precise unit cell parameters, actual elemental solid solution ratios, and multiple sets of original electrochemical long-cycle performance values, this invention differs from the extensive and unquantitative preparation processes of existing technologies. In terms of economic benefits, this invention replaces multi-step heat treatment with a one-step solid-state reaction, significantly reducing the total energy consumption and production cycle of high-temperature sintering. A small excess of aluminum powder in the raw materials can compensate for volatilization losses, eliminating the need for expensive organic solvents and special additives. Overall production costs are controllable. The resulting anode material has an ultra-long cycle life, reducing the frequency of energy storage battery replacements and lowering the total lifespan cost. Its high rate adaptability makes it suitable for high-power energy storage, fast-charging power batteries, and other high-end application markets, breaking through the limitations of existing low-element MABs. The bottleneck of insufficient energy storage performance in the phase is difficult to commercialize. The standardized and replicable process route is suitable for small-batch preparation in the laboratory and the transformation of industrial continuous sintering production lines. In the future, high-performance energy storage devices can be developed based on pentaneous MAB phase materials, and the industrial chain of new layered boride functional materials can be expanded. It has significant industrial economic value and clean energy application market prospects.

[0104] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the invention.

[0105] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A pentagonal MAB phase solid solution material, characterized in that, The chemical formula of the pentagonal MAB phase solid solution material is M2AB2, where M is a transition metal selected from three of chromium, molybdenum, yttrium, iron, and manganese, the atomic radius ratio of the three transition metals is 0.9-0.95:1:1.2-1.3, the molar ratio of each transition metal is 0.9-1.2:0.9-1.2:1, A is aluminum, gallium, or indium, and the pentagonal MAB phase solid solution material has a hexagonal crystal system.

2. The pentagonal MAB phase solid solution material according to claim 1, characterized in that, The pentagonal MAB phase solid solution material belongs to the space group P63 / mmc and has the chemical formula Cr. 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2, Fe 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 or Mn 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2.

3. The pentagonal MAB phase solid solution material according to claim 1, characterized in that, When the chemical formula of the pentagonal MAB phase solid solution material is Cr 2 / 3 Mo 2 / 3 Y 2 / 3 AlB2 has a layered crystal structure with alternating MB and Al layers along the c-axis. The unit cell parameters are: a=5.38 Å, b=5.38 Å, c=22.39 Å, α=90°, β=90°, γ=120°.

4. A method for preparing a pentagonal MAB phase solid solution material according to any one of claims 1 to 3, characterized in that, Includes the following steps: Based on the chemical formula M2AB2, transition metal powder, A powder, and boron powder were weighed; after mixing and grinding, they were subjected to wet ball milling and dried to obtain a mixed powder. The mixed powder is pressed into a green body, and then sintered at room temperature to 1200℃~1800℃ under a protective gas atmosphere to obtain a pentagonal MAB phase solid solution material.

5. The method for preparing the pentagonal MAB phase solid solution material according to claim 4, characterized in that, During the sintering process, argon is used as the protective gas. The temperature is increased to 700℃~900℃ at a rate of 3℃ / min~7℃ / min, and then increased to 1200℃~1800℃ at a rate of 2℃ / min~4℃ / min. The sintering holding time is 180min~220min.

6. The method for preparing the pentagonal MAB phase solid solution material according to claim 4, characterized in that, During the pressing process, the pressure is 15MPa~25MPa, the holding time is 2min~5min, and the density of the green body is ≥55%.

7. The method for preparing the pentagonal MAB phase solid solution material according to claim 4, characterized in that, The particle size of the transition metal powder, A powder, and boron powder is 200-300 mesh.

8. The method for preparing the pentagonal MAB phase solid solution material according to claim 4, characterized in that, During the wet ball milling process, anhydrous ethanol is used as the medium, the ball-to-material ratio is 4-6:1, the rotation speed is 200-300 r / min, and the milling time is 25-35 min.

9. A lithium-ion negative electrode sheet, characterized in that, Active materials, carbon black, and binders are mixed, and a solvent is added to grind them into a slurry. This slurry is then coated onto a substrate, and after removing the solvent, it is rolled to obtain a lithium-ion negative electrode sheet. The loading of the active material is 1.0 mg / cm³. 2 ~1.5mg / cm 2 The active material is the pentagonal MAB phase solid solution material as described in any one of claims 1 to 3.

10. The lithium-ion negative electrode sheet according to claim 9, characterized in that, The coating thickness is 80μm to 120μm, and the mass ratio of active material, carbon black and binder is 6 to 8: 2 to 4: 1.